Experimental investigation on behavior of SFRC beam column joints with and without Haunch effect - Murugesan, A.; Thirugnanam, G.S. (Journal of Structural Engineering, 2025)
Beam column joint is an important component of a reinforced concrete moment resisting frame and should be designed and detailed properly, especially when the frame is subjected to earthquake loading. Failure of beam column joints during earthquake is governed by bond and shear failure mechanism which are brittle in nature. Therefore, current international code of practices gives more importance to provide adequate anchorage to longitudinal bars and confinement of core concrete in resisting shear. Modern codes provide for reduction of seismic forces through provision of special ductility requirements. Details for achieving ductility in reinforced concrete structures are given in IS 13920-1993. In the present study, a two bay five storey reinforced cement concrete moment resisting frame for a general building has been analyzed and designed by using STAAD Pro as per IS 1893-2002 code procedures and detailed as per IS 13920-1993 recommendations. An exterior beam column joint has been modeled to 1/5th scale of the prototype and the specimen has been subjected to cyclic loading to study its behavior during earthquake loading. The experimental program consists of two SFRC interior beam-column joint specimens without and with haunch effect designated as SFRC and SFRCH respectively. The interior top middle joint beam – column joints are examined in terms of Load carrying capacity, Load-Deflection behavior, Stiffness degradation, Energy dissipation capacity, Ductility factor and cracking characteristics. A code IS 13920-1993 suggests provision of special ductility recommendations for the reduction of seismic forces. Based on the experimental results significant conclusions are drawn and the advantage of using haunch effect in the beam-column joint region has been established.